Overview Role of Simulation Package in Virtual Manufacturing and for CNC Machinery - Mahesh, R.; Murali, J. Ganesh; Arulmurugan, R. (International Journal of Engineering and Technology, 2018)
Computer Numerical Control Machines (CNC) totally changed the scenario in manufacturing industries in terms of production volume, easy flexibility and with fewer deviations. As customers expect high grade of accuracy, precision, reliable and prompt supply it became essential in the manufacturing sector to reduce the time for developing and proving out new products. Normally programming and proving out the same plays a significant role in the product development cycle. Nowadays several software packages are there to stimulate the tool path, sequence of operations and validation of the program to ensure flawless performance. These packages do serve additional role of optimizing the program sequence and reduce the cycle time involved to manufacture the parts concerned.